Reflections on the Normative Power of the (Im)possible - Ottomar Bahrs (Journal of Alternative, Complementary & Integrative Medicine, 2026)
When medical sociologist Aaron Antonovsky analysed interviews with women going through menopause, he discovered something unexpected